Modeling of a DVB-S.2 link with LDPC coding / Suhailawati Ahmad Said - Ahmad Said, Suhailawati
This technical paper presents the modeling and analysis of DVB-S.2 link with LDPC coding, particularly to determine the best modulation scheme for this type of communication link. This project used the MATLAB 7.5.0 (R2007b) software to model and simulates the DVBS. 2 link with LDPC coding. Through this software, the value of bit error rate (BER) was obtained by adjusting the value of Es/No which is in the range of -30 to 30 and the QPSK modulation scheme. This QPSK modulation scheme that was used in this software is 1/2, 1/3, 2/3, 2/5 and 3/5. From the simulation, 1/3 QPSK modulation was found to be the best modulation scheme because of its low BER.